2015
DOI: 10.21608/avmj.2015.170256
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Some Antibiotics; Disinfectants and Antiseptics Efficacy Against Some Species of Pathogenic Bacteria

Abstract: İn this study the efficiency of four types of routinely used commercial disinfectant and antiseptics (Ethanol 70%, Dettol -Chloroxylenol-5%, Hibitine -Chlorohexidine gluconate-6% and Bleach (Sodium hypochlorite 10%) which used in the laboratory of microbiology in College of veterinary medicine, Mosul, Iraq were tested against four different bacterial strains which isolated from clinical specimens of infected animals (E.coli, Pseudomonas aeruginosa, Staphylococcus arueus and Corynebacterium renale). Antibiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Figures 4 and 5). Also,AL-Dabbagh et al (2015) found after 5 minutes of the exposure to the different concentration of Ethanol and Dettol, Dettol was less activity against P. aeruginosa than Ethanol Tashiro et al (2014). revealed low concentrations of Ethanol increase initial biofilm formation in P. aeruginosa after Ethanol treatment of planktonic bacteria.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Figures 4 and 5). Also,AL-Dabbagh et al (2015) found after 5 minutes of the exposure to the different concentration of Ethanol and Dettol, Dettol was less activity against P. aeruginosa than Ethanol Tashiro et al (2014). revealed low concentrations of Ethanol increase initial biofilm formation in P. aeruginosa after Ethanol treatment of planktonic bacteria.…”
mentioning
confidence: 85%
“…Ethanol, Dettol, chlorohexidin and soap are the most often used disinfectants in microbiology labs. As a dehydrating agent, ethanol damages cell membranes, causes protein denaturalization and induces cell lysis (AL-Dabbagh, Ali, Khalil, & Hamad, 2015). It is used in a number of settings to disinfect skin, medical equipment and cooking equipment since it is volatile, leaves little residue and is safe even if used orally.…”
Section: Introductionmentioning
confidence: 99%